Randomized Trial of Harp Therapy During In Vitro Fertilization–Embryo Transfer - Erin M. Murphy MD; Jennifer Nichols DO; Steve G. Somkuti MD, PhD; Michael Sobel DO; Andrea Braverman PhD; Larry I. Barmat MD (Journal of Evidence-Based Complementary & Alternative Medicine, 2014)
Objective: This study evaluated whether harp therapy reduces levels of stress and improves clinical outcomes in patients undergoing embryo transfer. Design: This prospective randomized trial enrolled 181 women undergoing embryo transfer, who were randomized to harp therapy during embryo transfer or standard treatment. Patients underwent standardized psychological testing and physiologic assessment of stress. Setting: The study was conducted in a reproductive medicine practice. Results: No statistically significant differences were found in the heart and respiratory rates, nor was there a significant difference in event-based anxiety at baseline. Harp therapy had a significantly larger decrease in state anxiety from pre– to post–embryo transfer. Clinical pregnancy was 53% versus 48% for the harp therapy and standard treatment groups, respectively. Conclusion: Harp therapy decreases state, or event-based, anxiety, significantly lowering state scores posttransfer and having a positive effect on acute levels of stress. There was an increased pregnancy rate, but larger sample sizes are needed to evaluate whether harp therapy has an effect on clinical outcomes.